Adsorption of Brilliant Scarlet 3r dye onto Corn Silk as Agricultural Waste in Neutral Medium - AL-Mammar, Dunya Edan (Iraqi Journal of Science, 2024)
This study investigates the adsorption of Brilliant Scarlet 3r dye (BS 3r) onto corn silk (CK), an agricultural waste, in a neutral medium. The characteristics of corn silk as an adsorbent were analyzed using Fourier transform infrared spectroscopy (FTIR) and Atomic force microscopy (AFM). Batch adsorption experiments were conducted to examine the effects of corn silk weight, initial BS 3r concentration, adsorption period, adsorption temperature, and pH of the medium on the adsorption process. Langmuir, Freundlich and Dubinin-Radushkevich (D-R) isotherms models were used to represented the equilibrium experimental date, the obtained values of correlation coefficient R2 indicated that the adsorption followed the Langmuir isotherm. The kinetics analysis results showed that the adsorption of Brilliant Scarlet 3r dye (BS 3r) onto corn silk followed the pseudo second-order model (PSOM), indicating its suitability for describing the adsorption kinetics. Thermodynamic parameters, including ∆G˚, ∆H˚, and ∆S˚, indicated that the adsorption process of BS 3r dye onto corn silk was spontaneous and exothermic in nature.